Training for community-based rangeland health workers - Ebro, Abule; Eba, Bedasa; Said, Mohammed Yahya; Lya, Golicha; Abdi, H. (International Livestock Research Institute, 2025)
This report summarizes a training for community-based rangeland health workers undertaken in Moyale, Oromia region, Ethiopia, from 30 September to 5 October 2024.